Molecular basis for the specification of floral organs by APETALA3 and PISTILLATA - Wuest, Samuel E. (National Academy of Sciences, 2012)
How different organs are formed from small sets of undifferentiated precursor cells is a key question in developmental biology. To understand the molecular mechanisms underlying organ specification in plants, we studied the function of the homeotic selector genes APETALA3 (AP3) and PISTILLATA (PI), which control the formation of petals and stamens during Arabidopsis flower development. To this end, we characterized the activities of the transcription factors that AP3 and PI encode throughout flower development by using perturbation assays as well as transcript profiling and genomewide localization studies, in combination with a floral induction system that allows a stage-specific analysis of flower development by genomic technologies. We discovered considerable spatial and temporal differences in the requirement for AP3/PI activity during flower formation and show that they control different sets of genes at distinct phases of flower development. The genomewide identification of target genes revealed that AP3/PI act as bifunctional transcription factors: they activate genes involved in the control of numerous developmental processes required for organogenesis and repress key regulators of carpel formation. Our results imply considerable changes in the composition and topology of the gene network controlled by AP3/PI during the course of flower development. We discuss our results in light of a model for the mechanism underlying sex-determination in seed plants, in which AP3/PI orthologues might act as a switch between the activation of male and the repression of female development.